What Is a White Epistemology in Psychological Science? A Critical Race-Theoretical Analysis - Teo, Thomas (Frontiers in Psychology, 2022)
Critical race theory guides the analysis of the nature of a white epistemology in psychological science, the consequences for the study of race, and how scientific racism has been possible in the pursuit of knowledge. The article argues that race has not only been misused in the politics of psychology but misappropriated because of the logic of psychological science. The epistemic process is divided into four components to argue that naïve empiricist approaches in psychology, centered on scientific method, prevent an intricate understanding of race. Reasons for privileging method in psychology and the consequences of a white epistemology are discussed, including a narrow epistemic horizon and an inability to account for the temporality and contextuality of psychological phenomena. Ignorance, failure, or unwillingness to account for epistemic complexity when studying race are identified as problems. Questions about who benefits from narrow epistemologies are answered and suggestions for a broader practice of knowledge and education are provided.